Lapatinib in combination with capecitabine in the management of ErbB2-positive (HER2-positive) advanced breast cancer - Bella Kaufman (Dove Medical Press, 2008)
Bella Kaufman1, Steven Stein2, Michelle A Casey2, Beth O Newstat21Sackler Faculty of Medicine, Tel Aviv University, Tel Aviv, Israel; 2GlaxoSmithKline, Collegeville, PA, USAAbstract: Lapatinib is an oral, reversible, dual inhibitor of epidermal growth factor receptor ErbB1 (EGFR) and human epidermal growth factor receptor type 2 ErbB2 (HER2). Results of a phase III study comparing lapatinib plus capecitabine with capecitabine alone in women with ErbB2-overexpressing advanced breast cancer previously treated with an anthracycline, a taxane, and trastuzumab were reported early based on superiority of the combination in prolonging time to tumor progression (TTP). An updated analysis in 399 women supports the earlier findings. In this updated analysis, TTP (hazard ratio [HR] 0.57) favored lapatinib plus capecitabine. Survival trended in favor of the combination. The incidence of cardiac events was numerically higher in the combination arm (5 cases in the combination arm, 2 cases in the monotherapy arm).Keywords: lapatinib, capecitabine, breast cancer, HER2